Wealth Inequality and Economic Growth: Evidence from the World Inequality Database - Rachel Steenbrink; Ahmed Skali (Global Labor Organization (GLO), 2024)
Although it is often argued that wealth inequality matters more for economic growth than income inequality, this relationship has rarely been studied empirically, with a few exceptions covering a very restricted country sample or short timeframe. Leveraging hitherto unexploited wealth inequality data from the World Inequality Database, covering a panel of 165 countries between 1995 and 2019, we document a negative and statistically significant relationship between wealth concentration at the top of the distribution and economic growth. A one standard deviation increase in wealth inequality within countries is associated with a 0.4 percentage points (17%) decline in growth rates. Instrumental variables support a causal interpretation of the results. The results survive a large battery of robustness checks, and we find little evidence to suggest a heterogeneous relationship.
Keywords: D31; D63; O10; O47; 330; Wealth Inequality; Economic Growth; Economic Development